2016
DOI: 10.4137/sti.s29901
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Action in ER-Negative Breast Cancer

Abstract: Breast cancer is a highly heterogeneous disease. Tamoxifen is a selective estrogen receptor (ER) modulator and is mainly indicated for the treatment of breast cancer in postmenopausal women and postsurgery neoadjuvant therapy in ER-positive breast cancers. Interestingly, 5–10% of the ER-negative breast cancers have also shown sensitivity to tamoxifen treatment. The involvement of molecular markers and/or signaling pathways independent of ER signaling has been implicated in tamoxifen sensitivity in the ER-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 92 publications
3
70
0
2
Order By: Relevance
“…Furthermore, characteristics, other than bone density, could be associated with the bone quality and health required to prevent fractures . The sensitivity of some patients with estrogen receptor‐negative breast cancer to tamoxifen showed at a possible complicated occult biochemical association between tamoxifen and hip fracture in patients with breast cancer …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, characteristics, other than bone density, could be associated with the bone quality and health required to prevent fractures . The sensitivity of some patients with estrogen receptor‐negative breast cancer to tamoxifen showed at a possible complicated occult biochemical association between tamoxifen and hip fracture in patients with breast cancer …”
Section: Discussionmentioning
confidence: 99%
“…23 The sensitivity of some patients with estrogen receptor-negative breast cancer to tamoxifen showed at a possible complicated occult biochemical association between tamoxifen and hip fracture in patients with breast cancer. 16,24 Muscle weakness in older women with breast cancer could be another factor associated with risk of hip fracture. Patients treated with tamoxifen were estrogen receptor-positive.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, downregulation of AKT through expression of the TGFB growth factor was described as an off-target effect of tamoxifen. 49,51 Of importance, Liu et al 44 showed an induced sensitivity to tamoxifen in the triple-negative breast cancer cell line HCC-1937, when re-activating PP2A using forskolin. This suggests the potential for use of combinatory therapy for BCER+ with membranous CIP2A staining.…”
Section: Discussionmentioning
confidence: 99%
“…46 Transforming growth factor beta (TGFB) has also been known to interact with PP2A, which might contribute to the contradictory regulation of p-AKT and MYC. [47][48][49] In metastatic breast cancer (MDA-MB-231), the transition of tumour-suppressive role to tumour-promoting role of TGFB has been attributed to the nuclear factor of activated T-cells (NFAT), which is shown to drive epithelial-to-mesenchymal transition (EMT) and c-MYC expression. 50 Here, we suggest another potential mechanism for this transition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many chemotherapeutic drugs such as tamoxifen, which are used to treat certain types of breast cancer, are not effective against triple negative cells. This is because tamoxifen selectively binds to estrogen receptors, which in turn prevents estrogen from attaching to its receptor (Manna and Holz, 2016). Estrogen is required for some breast cancer cells to grow; hence, blocking the hormone will prevent the tumor *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%